Management of persistently aphid-transmitted faba bean viruses in Tunisia - Najar, Asma; Mghandef, Samia; Kumari, Safaa (International Center for Agricultural Research in the Dry Areas, 2024)
Faba bean is the most important cool season legume crops grown in Tunisia. Productivity is affected by several biotic factors including viruses. Most plant viruses are transmitted by several aphid species and therefore vector management is one of the main options for controlling them. On-farm experiments were conducted at Menzel Bourguiba and Mornag INRAT Station during the 2023/2024 growing season to manage faba bean viruses and their aphid vectors. Two faba bean varieties (Najeh and Chourouk), two planting dates, and seed treatment with two doses of Cruiser® (Thiamethoxam) (1.00 and 1.2 cc/kg) compared to untreated seeds (control) were used as treatments. The results showed that no virus infection was detected in plots with the 1st planting date and plots treated with Cruiser on the 2nd planting date at both sites, whereas viruses were detected at low rate (0.4-0.7%) in untreated plots only on the 2nd planting date. Both faba bean varieties (Chourouk and Najeh) produced significantly higher yields than the untreated control for both doses of Cruiser. Low rainfall and high temperature during the 2023/2024 growing season at both sites negatively affected aphid activity and hence virus infection, but the results obtained indicated that the virus and aphid vector management could be achieved by adjusting the planting date of faba bean crops and seed treatment with Cruiser.